Electronic cigarettes: A narrative review of the implications for the pediatric anesthesiologist. Issue 6 (5th May 2020) - Lemay, Francois; Baker, Paul; McRobbie, Hayden
Abstract: The use of electronic cigarettes (EC) is increasing and the number of EC publications is rapidly growing. While some health organizations focus on the harmful effects of using EC (vaping), others promote the benefits of ECs as a less harmful alternative to smoking tobacco. There is concern that vaping might have adverse respiratory consequences for pediatric patients facing anesthesia and intensive care. This narrative review summarizes current knowledge and recommendations regarding the risks of EC relevant to the anesthesiologist and the use of ECs as a step‐down option from tobacco. We provide guidance on the management of vaping patients in the perioperative period.